Determining Coefficient of Discharge to Compare Coefficients of Resistance for Different Coarse Aggregate Beds - Shambo, M. T; Deepak, Tirumishi Jada; Bategeleza, Joyce Edwin; Abdulhakeem, Nasir (International Journal of Scientific Research in Science, Engineering and Technology, 2015)
The paper is an investigation to determine the coefficient of discharge for different notches and weirs with coarse aggregate beds and then comparing Chezy’s, Darcy Weisbach’s and the Manning’s coefficients. Prior to that, the notches had to be designed and fabricated, then experiments were conducted. Six methods were used for this experiment. The open channel on the hydraulic bench is intended to depict an actual open channel flow scenario, but on a small scale, steady flow was used for these experiments. From this investigation, it was confirmed that discharge coefficient for all notches and weirs ranges between 0.57-0.9. The bed of a channel, in this case, coarse aggregates was found to have an effect on discharge coefficient, though it is said to be insignificant. Manning’s n and Darcy-Weisbach’s f were found to decrease with increase in discharge and velocity.